Trend of Non-Pharmacological Therapy for First Phase of Active Labor Pain: A Pilot Study - Gunadi, Agus; Prihartono, Nurhayati Adnan (Jurnal Epidemiologi Kesehatan Indonesia, 2022)
There are several of non-pharmacological therapies to be used as caring practice to mother with labor pain. This study aimed to observe the effectiveness of both single and combination therapy of warm compresses and counter pressure massage (CPM) for the management of labor pain during the first active phase through medical records. This is a pilot study that used a cohort prospective design. The total number of respondents was 90 respondents, divided into 3 groups based on the non-pharmacological therapy that was given by the midwives or nurses. Pain level was measured with NRS 11. The study was conducted at PKU Muhammadiyah Gamping Hospital from May 2020 to September 2020. A comparative hypothesis analysis was done to compare the Pretest-Posttest of pain level between groups using the Wilcoxon, Kruskal-Wallis, and Post hoc Mann-Whitney tests with a significance of p <0.05. There was a reduction of 1.53 pain level of subject who received CPM, 1.16 by received warm compress and 1.67 for those who received combination therapy. It was found there was a significant difference between three groups with p=0.020. It was found that CPM was compared to Warm compress obtained p=0.017, CPM compared to Combination therapy obtained p=0.019, warm compress compared to combination therapy obtained p = 0.396.Combination therapy showed the highest reduction effect toward pain level of First Phase of Active Labor Pain. However, the CPM therapy showed to achieve effectiveness compared to warm compress and combination therapy.